Palliative nursing care for the elderly surgical patient: scoping review protocol (Research, Society and Development, 2023)
This article presents the scoping review protocol on the provision of palliative care for older adults in the perioperative setting by nursing, with the recognition of the diversity of needs across the continuum of living and dying well for older adults. The protocol aims to document the processes involved in the planning and methodological conduct of an extensive scoping review, which aims to map and identify in the literature the existing productions on nursing actions aimed at palliative care for the elderly patient in the context of surgical hospitalization. The study will be descriptive, exploratory, scoping review, to be carried out in six databases and two collections of gray literature, guided by the guidelines of the Joanna Briggs Institute (JBI). The review protocol was elaborated following the Preferred Reporting Items for Systematic Review - Scoping Review (PRISMA-ScR) and publications restricted to the elderly public, hospitalized in Surgical Clinic/Surgical Intensive Care Units, eligible or receiving palliative nursing care will be included. Data will be extracted and processed in 3 stages, compiled in Rayyan® software, by 2 independent reviewers and 1 decision maker. The protocol was registered in the Open Science Framework (OSF), and thus it is expected to identify the needs and priorities of nursing interventions in palliative care for the surgical elderly, as well as to foster a more socially connected, planned and person-centered care.